2014
DOI: 10.1186/1471-2490-14-74
|View full text |Cite
|
Sign up to set email alerts
|

Renal surgery for kidney cancer in Germany 2005–2006: length of stay, risk of postoperative complications and in-hospital death

Abstract: BackgroundRepresentative statistics of surgical care among patients with kidney cancer are scant. With the introduction of the diagnosis related group system in Germany, it is now possible to provide nationwide statistics on surgical care. We studied in-hospital mortality risk in relation to comorbidity and complications, length of hospital stay in relation to surgical approach and comorbidity, and risk of complications in relation to surgical approach among kidney cancer patients undergoing nephrectomy.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…A considerable rate of severe complications occurred in the postoperative period. The complication rates are comparable to previous reports (i.e., Stang et al reported an intrahospital mortality of 1.4% patients undergoing nephrectomy for the treatment of renal cancer in Germany in a 2-year period [ 30 ]). In a large contemporary cohort of 3644 CN-treated patients with mRCC from the USA, Palumbo et al showed an overall complication risk of 39.7–55.3%, stratified according to age groups.…”
Section: Discussionsupporting
confidence: 87%
“…A considerable rate of severe complications occurred in the postoperative period. The complication rates are comparable to previous reports (i.e., Stang et al reported an intrahospital mortality of 1.4% patients undergoing nephrectomy for the treatment of renal cancer in Germany in a 2-year period [ 30 ]). In a large contemporary cohort of 3644 CN-treated patients with mRCC from the USA, Palumbo et al showed an overall complication risk of 39.7–55.3%, stratified according to age groups.…”
Section: Discussionsupporting
confidence: 87%
“…Complications rates after PN and RN are reported to be 16-26% [210][211][212]. Major complications (defined as Clavien-Dindo ≥3) are reported to be 5.4% for PN and 3.1% for RN [203].…”
Section: Postoperative Complications 1672mentioning
confidence: 99%
“…To improve outcomes, it is important to avoid the "failure to rescue". Therefore, a department must postoperatively prevent complications, and organize the postoperative surveillance so that complications are caught early and treated by a competent specialist as soon as possible [203,210,212,220].…”
Section: Postoperative Complications 1672mentioning
confidence: 99%
“…Causes of death differ, but cardiac disease, infectious diseases, embolisms and bleeding are typically related[212,217]. Gastrointestinal and urologic complications were associated with IHM[210]. As described by Cloutier, tumor stage is determinant of TDM.…”
mentioning
confidence: 90%
See 1 more Smart Citation